Plants and therapeutics: Interaction - Shah Murad; Hafiz Moeen-; Farid-; Abdul Ghaffar; Seema Shah Murad; Jamila Shah; Manal Rauf Mahar (International Journal of Pharmaceutical Sciences and Developmental Research - Peertechz Publications, 2019)
Medicinal herbs are getting popularity due to their good compliance on the basis of their ethnic utilization and lesser side effects. Plasma lipids in body include, cholesterol, triglycerides, very low density lipoprotein-cholesterol, low density lipoprotein-cholesterol, and high density lipoprotein-cholesterol. High levels of LDL-cholesterol and lower levels of HDL-cholesterol may cause oxidation in plasma leading to formation of atherogenic plaques which are main etiological factors for development of Coronary Artery Diseases (CAD). Many hypolipidemic herbs are being used to prevent CAD. We have used AJWAIN, Alsi separately and in combination to observe their hypolipidemic potential. Study was conducted at Jinnah Hospital Lahore-Pakistan from March 2015 to July 2015. One hundred hyperlipidemic patients were selected from lipid research clinic of Jinnah Hospital, Lahore-Pakistan, and approved written consent was taken from all patients. They were divided in four equal groups comprising 25 patients in each group. Group-I was treated by AJWAIN for three months, Group-II was treated by ALSI, Group-III was treated by AJWAIN plus Alsi for the period of three months. After three months therapy it was observed that AJWAIN reduced LDL-cholesterol 23.77mg/dl and increased HDL-cholesterol 3.3mg/dl. ALSI reduced LDL-cholesterol 7.5mg/dl and increased HDL-cholesterol 5.3mg/dl. Whereas combination of both agents decreased LDL-cholesterol 16.1mg/dl and increased HDL-cholesterol 6.6mg/dl in three months therapy. It was concluded from this research work that ALSI and AJWAIN given separately or in combination, have good enough potential to reduce LDL-cholesterol but are less potent effect on HDL-cholesterol in hyperlipidemic patients.